THE COMPETITIVENESS OF SERBIAN AGRO-FOOD SECTOR - Đukić, Sanja; Tomaš-Simin, Mirela; Glavaš-Trbic, Danica (Economics of Agriculture, 2018)
The authors analyzed the the competitiveness of agro-food sector of Serbia. The main objectives of this research were: (1) determining the competitive position of the agro-food sector in Serbia within the European Union, and (2) identifying compatibility between the export of Serbian agro-food sector and import requests for the same products in the European Union. In this research, indices of comparative advantage (RCA, ARCA and RC) have been applied in order to identify the competitiveness of agro-food sector in Serbia. Considering the European Union is most important trade partner of Serbia, the paper gives a review of the complementarity of export products from the agro-food sector of Serbia, with imports of the same products to the EU. The authors conclude that the comparative advantages of agro-food sector in Serbia do not reflect the actual competitive position, and suggest key guidelines for its improvement.